(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
Globalization issue which according to its nature is rather complex and contradictory has been analyzed from various theoretical and conflicting aspects in the modern sociology. This paper analyses two theoretical attitudes on the globalization issue. The first one refers to globalization as a process, as properly articulated theoretical orientation which has found its full expression in the works of Immanuel Wallerstein (Wallerstein, 1999), Ronald Robertson (Robertson, 1992), Martin Albrow (Albrow, 1990), Anthony Gidens (Gidens, 1998) and Jan Pieterse (Pieterse, 2009). However, the most eloquently exponents of the theoretical orientation of the globalization as a process are reflected in the works of Pierre Bourdie (Bourdie, 1998), Paul Hirst, Grehejm Thomson (Hirst and Thompson, 1999, 2000) and George Soros (Soros, 2002). Both perspectives are extremely important for interpreting various sociocultural contexts.